The East Bengal Floods (1954 – 1956): A Comparative Historical Study - Begum, Shazeda (The Jahangirnagar Review Part-C, 2025)
This paper investigates the devastating flood that occurred in East Bengal between 1954 and 1956, focusing on the resulting socio-economic losses and the government's relief response. Caused by heavy monsoon rains and the overflow of the major rivers, the flood intensely affected the southeastern and central regions of East Bengal, including the districts of Chattogram, Barisal, Dhaka, Madaripur, Kishoreganj, Mymensingh, Patuakhali, Bhola, and Khulna. Vast areas were inundated, significantly damaging agricultural lands, housing, infrastructure, and other public facilities. The newly elected United Front Government faced immense challenges in managing relief operations constrained by limited resources and growing public dissatisfaction. Although relief was provided by the government, international, and voluntary sources, it was inadequate and often distributed inequitably due to political influence. The central Pakistani government also failed to respond effectively. Despite the magnitude of the floods, scholarly engagement with their long-term consequences remains limited. Despite the magnitude of the floods, scholarly engagement with their long-term consequences remains limited. This study, therefore, highlights the long-term consequences of the floods and the structural weaknesses in disaster governance that contribute to the broader struggle for regional autonomy and, eventually, the independence of Bangladesh.